2002
DOI: 10.1021/jp014733x
|View full text |Cite
|
Sign up to set email alerts
|

Charge Density Studies of Weak Interactions in Dipicrylamine

Abstract: A low-temperature high-resolution X-ray and neutron diffraction study of charge distribution in the superacid dipicrylamine (DPA) has been carried out. This structure exhibits interesting weak interactions including bifurcated N-H‚‚‚O and C-H‚‚‚O H-bonds which consolidate it. The corresponding interaction lines appear to be modified in the vicinity of the critical points of the covalent bonds of the hydrogen atoms. The presence of six nitro groups generates some short N‚‚‚O contacts. On the basis of the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…in a comparison with the σ‐hole on halogens and it explains the orthogonal geometry. Charge density analysis showed the presence of interaction lines and bond critical points (bcp) for such interactions, even at distances longer than the sum of van der Waals (vdW) contacts . Both types (σ‐ and π‐hole) are very similar in nature and the importance of the latter has been highlighted by Frontera and co‐workers .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…in a comparison with the σ‐hole on halogens and it explains the orthogonal geometry. Charge density analysis showed the presence of interaction lines and bond critical points (bcp) for such interactions, even at distances longer than the sum of van der Waals (vdW) contacts . Both types (σ‐ and π‐hole) are very similar in nature and the importance of the latter has been highlighted by Frontera and co‐workers .…”
Section: Introductionmentioning
confidence: 90%
“…Both types (σ‐ and π‐hole) are very similar in nature and the importance of the latter has been highlighted by Frontera and co‐workers . Carbonyl⋅⋅⋅ carbonyl contacts, studied by Diederich and co‐workers, and nitro⋅⋅⋅nitro orthogonal interactions, studied by Wozniak and co‐workers, are typical examples of such π‐hole‐based synthons. Carbonyl⋅⋅⋅carbonyl contacts in crystalline aldehydes are even more exciting as they are less studied from a crystal engineering perspective and certainly not in any property engineering of solids.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, crystal structures of DPA and a computational study on the intermolecular interactions observed in the crystal structure have been reported. [1] The crystal structures of some of its organic salts have also been reported.…”
Section: Dipicrylaminementioning
confidence: 99%
“…Similar non-bonded attractive interactions have been reported. [23] Binding Studies with DMSO and DMF In our attempt to resolve the 1 H NMR spectroscopic signals for the urea protons in receptors 2 and 3, the spectra for the respective receptors were recorded in [D 6 ]DMSO and [D 7 ]DMF. In both cases, broad and apparently downfield-shifted bands were observed.…”
Section: Resultsmentioning
confidence: 99%